Validitas Utrecht-Management Of Identity Commitments Scale (U-MICS) Versi Indonesia: Struktur Faktor, Invariansi Pengukuran Gender, dan Usia - Muttaqin, Darmawan (Faculty of Psychology, Universitas Gadjah Mada, 2017)
The purpose of this study was to examine the psychometric properties of the Indonesian version of the U-MICS, a measure three identity dimensions. Participants were 910 adolescents (12-21 years old). The Confirmatory Factor Analyses and Multi-Group Analyses were used to examine the factor structure, gender, and age measurement invariance of the Indonesian version of the U-MICS. We further tested the gender and age differences using Multivariate Analysis of Variance. The results indicated that the factor structure of Indonesia version of the U-MICS with a solution three factors was very fit with data and there was measurement invariance across gender and age groups. Gender and age differences in identity dimensions were also found. The results suggest that the Indonesian version of the U-MICS was a measurement tool that has the consistency of structure factors when used to measure the identity dimensions in Indonesian adolescents.Abstrak : Tujuan dari penelitian ini untuk menguji properti psikometris dari U-MICS versi Indonesia yang mengukur tiga dimensi identitas. Partisipan yang terlibat sebanyak 910 remaja (12-21 tahun). Analisis konfirmatori faktor dan analisis multi-kelompok digunakan untuk menguji struktur faktor, invariansi pengukuran gender, dan usia dari U-MICS versi Indonesia. Penulis menguji perbedaan gender dan usia dengan menggunakan analisis varians multivariat. Hasil analisis mengindikasikan bahwa struktur faktor dari U-MICS versi Indonesia dengan solusi tiga faktor sesuai dengan data dan terdapat invariansi pengukuran antar kelompok gender dan usia. Perbedaan gender dan usia pada dimensi identitas juga ditemukan. Hasil menunjukkan bahwa U-MICS versi Indonesia merupakan alat ukur yang memiliki konsistensi struktur faktor ketika digunakan untuk mengukur dimensi identitas pada remaja Indonesia.